2016
DOI: 10.1111/cdev.12621
|View full text |Cite
|
Sign up to set email alerts
|

Overt and Relational Victimization: A Meta‐Analytic Review of Their Overlap and Associations With Social–Psychological Adjustment

Abstract: This meta-analytic review includes 135 studies, representing 17 countries, of child and adolescent (ages 4-17) samples of overt and relational peer victimization and examines the magnitude of overlap between forms of victimization and associations with five social-psychological adjustment indices. Results indicate a strong intercorrelation between forms of victimization (r¯ = .72). No gender difference with regard to relational victimization was found, but boys were slightly higher in overt victimization. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
214
3
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(247 citation statements)
references
References 83 publications
24
214
3
6
Order By: Relevance
“…Among these risks, emotional distress has received the most empirical support. Victimization is significantly correlated with anxiety and depression, as well as with related constructs such as emotional sensitivity, low self‐esteem, neuroticism, and poor social skills (Casper & Card, 2017; Tsaousis, 2016; Zimmer‐Gembeck & Duffy, 2014). Although the majority of research has been cross‐sectional, sufficient longitudinal evidence has demonstrated bidirectional relationships between emotional distress and victimization across time (Karlsson, Stickley, Lindblad, Schwab‐Stone, & Ruchkin, 2014; Reijntjes, Kamphuis, Prinzie, & Telch, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among these risks, emotional distress has received the most empirical support. Victimization is significantly correlated with anxiety and depression, as well as with related constructs such as emotional sensitivity, low self‐esteem, neuroticism, and poor social skills (Casper & Card, 2017; Tsaousis, 2016; Zimmer‐Gembeck & Duffy, 2014). Although the majority of research has been cross‐sectional, sufficient longitudinal evidence has demonstrated bidirectional relationships between emotional distress and victimization across time (Karlsson, Stickley, Lindblad, Schwab‐Stone, & Ruchkin, 2014; Reijntjes, Kamphuis, Prinzie, & Telch, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Large‐scale, cross‐national studies have estimated that about one‐third of adolescents are involved in some forms of victimization by peers . Research has also widely confirmed that peer victimization in school is associated with a variety of psychological problems, such as anxiety, depression, loneliness, low self‐esteem, and suicidal ideation . To date, 3 meta‐analyses have also shown that being victimized is significantly associated with more frequent somatic symptoms, such as headaches, stomachaches, muscle pains, poor appetite, vomiting, and many others .…”
mentioning
confidence: 99%
“…Both types of victimization also predicted increases in internalizing problems over time. Past research also shows experiences of peer victimization in adolescence are associated with poorer mental health (e.g., internalizing and externalizing symptoms; Casper & Card, ; Reijntjes et al., ; Reijntjes, Kamphuis, Prinzie, & Telch, ; Ttofi, Farrington, Losel, & Loeber, ).…”
Section: Peer Victimization and Mental Health And Substance Usementioning
confidence: 99%
“…Considerable research demonstrates associations between physical and relational peer victimization and aspects of both mental and physical health in adolescence (see Arseneault, Bowes, & Shakoor, ; Card & Hodges, ; Casper & Card, ; McDougall & Vaillancourt, for reviews). Peer victimization has been conceptualized as a chronic stressor (McDougall & Vaillancourt, ; Vaillancourt, Hymel, & McDougall, ) that can negatively impact health outcomes over time (Takizawa, Maughan, & Arseneault, ; Wolke, Copeland, Angold, & Costello, ).…”
Section: Adolescent Patterns Of Peer Victimization: Concurrent and Lomentioning
confidence: 99%